Becoming roller derby grrrls: Exploring the gendered play of affect in mediated sport cultures. (December 2013) - Pavlidis, Adele; Fullagar, Simone
This article explores how the global revival of roller derby as an alternative sport for women has been mobilised through online social networks, league promotion and fan sites that create imagined communities of 'roller grrrls'. In the creation of sport culture we argue that the virtual performance of 'derby' identities is as significant as the embodiment of play. Like other sports, derby sites mobilise affect (passion, pleasure, pain, desire to play) through a discourse of 'empowerment' that urges women to overcome limits and reinvent gendered subjectivity. However, within the virtual space of roller derby, complex affects are produced and circulated within power relations that can include or exclude. Through an analysis of the way affect is mobilised in selected roller derby sites, we identify how virtual sport identities are connected through the movement of 'affects' across bodies and leagues. These affects both circumscribe and undermine the notion of a single derby community.